Antibacterial activity lemongrass leaves of Staphylococcus aureus inhibition one - Yunita Yunita; Fitria Lestari; Yuli Febrianti (JPBIO (Jurnal Pendidikan Biologi), 2020)
Staphylococcus aureus is a nosocomial problem that can cause skin infections. Treatment of skin infections can be done by using citronella (Cymbopogon nardus) which is antibacterial because it contains compounds such as flavonoids, steroids, terpenoids, saponins, and essential oils. This study aims to determine the antibacterial power of Cymbopogon nardus leaf starch essence against Staphylococcus aureus inhibition zone. This type of research is a laboratory experiment using a post-test only control group design. The results showed that the extract of Cymbopogon nardus leaves with a concentration of 5%, 10%, 15%, and 20% with positive control of ampicillin had different inhibitory zona against Staphylococcus aureus bacteria. The conclusion is that the concentration of Cymbopogon nardus leaf starch is the most effective and forms an inhibition zone with the largest average (16.28), namely a concentration of 20%.Keywords: Antibacterial, lemongrass, Staphylococcus aureus